Insights into the principles, design methodology and applications of electrocatalysts towards hydrogen evolution reaction - Jie Xiong (Elsevier, 2021)
The electrolysis of water for sustainable hydrogen producing is a crucial segment of various emerging clean-energy technologies. However, pursuing an efficient and cheap alternative catalyst to substitute state-of-the-art platinum-group electrocatalysts remains a prerequisite for the commercialization of this technology. Typically, precious-metal-free catalysts have always much lower activities towards hydrogen production than that of Pt-group catalysts. To explore high-performance catalysts, maximally exposed active sites, rapid charge transfer ability and desirable electronic configuration are essentially demanded. Herein, the fundamentals of hydrogen evolution reaction will be briefly described and the main focus will be on the interfacial engineering strategies by means of constructing defect structure, creating heterojunction, phase engineering, lattice strain control, designing hierarchical architecture and doping heteroatoms to effectively proliferate the catalytic active sites, facilitate the electron diffusion and regulate the electronic configuration of numerous transition metals and their nitrides, carbides, sulfides, phosphides as well as oxides, achieving a benchmark performance of platinum-free electrocatalysts for the hydrogen evolution reaction. This review unambiguously offers proof that the conventional cheap and earth-abundant transition metal-based substances can be translated into an active water splitting catalyst by the rational and controllable interfacial designing.